PILIHAN POLITIK PEMILIH PEMULA PADA PEMILU LEGISLATIF 2014 - Rofieq, Ainur (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2016)
Any elections there is always a novice group criteria voters the age of 17 years old and upward or has been married at the time of the election was held. Existing reality shows that’s voters novice possessed of different characteristics with groups of voters and it has been choose. Question of the research are how political choice a student on the legislative election 2014 and what political factors inform the choices a student on the legislative election 2014. The results show that voters choice novice based by a factor of political vision and mission candidates. In addition in determining the choice is novice based on the consideration of the voters own.